A reply to the comment on "control of bovine mastitis in the 21st century: Immunize or tolerize?" by Fernando N. Souza and co-workers. (October 2019) - Amadori, M.; Addis, M.F.; Bronzo, V.; Castiglioni, B.; Moroni, P.; Piccinini, R.
Highlights: There is strong evidence of a microbiome in bovine milk. The milk microbiome demands tolerance to dwelling bacterial species. Bovine udder is poised to a non-inflammatory control of bacterial pathogens. The IgA response can underlie effective mucosal immunization. Immunostimulation and reduced metabolic stress are useful complements.